Gender Inequalities in Access to Tuberculosis Services in South Africa - Haji, Mina (Department of Public Health and Family Medicine, 2020)
Tuberculosis (TB) is the leading natural cause of mortality in South Africa, and the country has the sixth-highest TB burden in the world. Of every 100 000 South Africans, 781 are expected to develop TB. Even with the adoption of the Directly Observed Treatment, Short-Course (DOTS) strategy since 1996 and substantial investments and improvement in TB control, South Africa has failed to meet the TB-related targets set by the World Health Organization (WHO). The current burden of TB will lead to massive consequences of mortality and morbidity in the country besides the substantial financial implications for the health system. Considering the infectious nature of TB as a communicable disease, for the sake of controlling the level and spread of the disease as well as preventing drug resistance, adherence to treatment is essential. Moreover, the burden of non-adherence to TB treatment has been affirmed as one of the primary challenges facing global control of TB pandemic. The accessibility of needed care influences the adherence to treatment and in a situation in which non-adherence is the consequence of unjust and avoidable forces, the equity issue inflates its importance. Both barriers and facilitating factors to access and adherence to TB treatment are affected by different social determinants of health, inclusive of gender. Generally, the gender aspects of access to TB services have been an overlooked research area, and insufficient attention has been given to this aspect of TB control; although a number of previous studies, which had attempted to examine the association between gender and access barriers to TB treatment in different contexts, reported gender as a crucial factor in access to TB services. Hence, this dissertation aimed to explore the gender-based inequalities in access and adherence to TB services in South Africa, from the perspective of TB patients. This study relies on data drawn from the Researching Equity in Access to Health Care (REACH) project. Applying a comprehensive framework of access, interviews were conducted with 1229 TB patients from four health sub-districts in South Africa, to assess gender-related inequalities across the access dimensions of affordability, acceptability and availability of TB services. Descriptive statistics were computed, and comparisons of access barriers and adherence between men and women were explored using multivariate linear and logistic regressions. Based on the results, there was no significant association between levels of adherence and gender (all p-values> 0.05). Among availability-related variables, men spent significantly less time at the clinic to fetch TB medication (coefficient, -7.06; 95% CI, [-13.5, -0.7]); however with regards to affordability-related variables, men were significantly less likely to receive a disability grant (AOR, 0.48; 95% CI, [0.36, 0.63]), and among acceptability-related variables men were significantly less likely to judge the length of queues to be too long or the cleanliness of the facility to be substandard (AOR, 0.69; 95% CI, [0.52, 0.91], and AOR, 0.67; 95% CI, [0.46, 0.97], respectively). Overall, our findings suggest that there is no association between the level of adherence to TB treatment and gender. Moreover, there was no evidence of systematic gender-based disparities in access to TB services. However, the findings reveal concerns about the condition and cleanliness of health facilities that may impact the patients' adherence and be a barrier, specifically, in women's use of TB services.